2009
DOI: 10.1104/pp.109.140798
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of REP27 Protein Action in the D1 Protein Turnover and Photosystem II Repair from Photodamage    

Abstract: The function of the REP27 protein (GenBank accession no. EF127650) in the photosystem II (PSII) repair process was elucidated. REP27 is a nucleus-encoded and chloroplast-targeted protein containing two tetratricopeptide repeat (TPR) motifs, two putative transmembrane domains, and an extended carboxyl (C)-terminal region. Cell fractionation and western-blot analysis localized the REP27 protein in the Chlamydomonas reinhardtii chloroplast thylakoids. A folding model for REP27 suggested chloroplast stroma localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 60 publications
2
14
0
2
Order By: Relevance
“…To determine protein content in samples treated with Cd, we used determined amount of Chl (0.5 mg total Chl loaded on the gel) as in Dewez et al (2009). Thylakoids of control and cadmium-treated cells were isolated using glass beads and resuspended in isolation buffer (50 mM tricine, 10 mM NaCl, 5 mM MgCl 2 , pH 7.8) (Morgan et al 1998).…”
Section: Sds-polyacrylamide Gel Electrophoresis and Western Blottingmentioning
confidence: 99%
“…To determine protein content in samples treated with Cd, we used determined amount of Chl (0.5 mg total Chl loaded on the gel) as in Dewez et al (2009). Thylakoids of control and cadmium-treated cells were isolated using glass beads and resuspended in isolation buffer (50 mM tricine, 10 mM NaCl, 5 mM MgCl 2 , pH 7.8) (Morgan et al 1998).…”
Section: Sds-polyacrylamide Gel Electrophoresis and Western Blottingmentioning
confidence: 99%
“…Presumably, therefore, the roles of these factors in PSII biogenesis or maintenance have been retained during evolution. In contrast, other factors are specific to cyanobacteria, such as PROCESSING ASSOCIATED TPR PRO-TEIN (Schottkowski et al, 2009), Slr0286 (Kufryk and Vermaas, 2001), and Slr2013 (Kufryk and Vermaas, 2003), or specific to higher plants, such as LOW PSII ACCUMULATION1 (LPA1)/PSII REPAIR27 (Park et al, 2007;Dewez et al, 2009) and LPA2 , which may represent evolutionary adaptations to specific environments. Notably, LOW QUANTUM YIELD OF PHOTOSYNSTEM II1 (LQY1), a small thylakoid zinc-finger protein exclusive to land plants, was also recently found to be involved in the repair cycle and reassembly of PSII .…”
Section: Introductionmentioning
confidence: 99%
“…HCF136 predominantly associates with a very early PSII assembly complex containing D2, PsbE, and PsbF (Plü cken et al, 2002), and YCF48, the Synechocystis HCF136 homolog, has been detected in RC, where it interacts with unassembled pD1 (Komenda et al, 2008). In Arabidopsis, LPA1 binds to D1 during de novo biogenesis of PSII (Peng et al, 2006), whereas its Chlamydomonas ortholog, REP27, has also been suggested to play a role in D1 synthesis, albeit during PSII repair rather than during assembly (Park et al, 2007;Dewez et al, 2009). The Arabidopsis LPA2, which has no counterpart in cyanobacteria or Chlamydomonas, interacts specifically with CP43 and ALB3 (Ma et al, 2007).…”
Section: Introductionmentioning
confidence: 99%